Specifics of designing the electroplating area of a service facility - Sinitsky, D. (Запоріжжя: ТДАТУ, 2026)
The electroplating section is intended for restoring parts using electrolytic coatings, as well as for applying decorative and anticorrosive coatings. To increase the wear resistance of parts, chromium plating and iron plating are used; for anticorrosion protection – zinc plating; for protective and decorative finishing – chromium plating, nickel plating, and copper plating. The basis for designing the section is the production program.
Keywords: electroplating area; chromium plating; production program